Agricultural land measures for climate change adaptation in arid regions: Can the farmers do it alone? - Al-Kilani, Muhammad Rasool (Journal of Aridland Agriculture, 2024)
Climate change has become an unequivocal issue; changing precipitation patterns and climate variability will have disastrous impacts on the fragile agricultural land resources of arid regions. Farmers, equipped with indigenous knowledge and readily available resources, are the most direct stakeholder interacting with agricultural lands; examining farmers’ capacity to successfully implement farm-level adaptive measures is a pressing matter. This paper provides an overview on various agricultural measures for climate change adaptation in arid regions and discusses some major relevant constrains and the extent of farmers’ capabilities to implement such strategies. Various techniques such as shifting sowing dates, conservation agriculture, and rainwater harvesting have shown potential to serve as adaptive strategies. These can help reduce crop failure risks, improve soil moisture conservation and increase water availability for crops, and could help adapt to precipitation variability in arid regions. However there is strong evidence that many farmers in arid regions may not be able to implement such strategies successfully as adaptive measures and there is no clear evidence that climate variability is currently less of a risk with existence of such measures. This can be attributed to the various constraints such as the need for reliable access to resources, climatic data, and research output by farmers for successful implementation. These constraints could be circumvented by institutional-level measures such as agricultural subsidies, relevant and dynamic policies, and programs. Overwhelming evidence suggests that this is only possible by involvement of various stakeholders in the planning process such as researchers, farmers and the private sector.